Screening Support of Bimetallic Ruthenium-Tin Catalysts for Aqueous Phase Hydrogenolysis of Furfuryl Alcohol to 1,5-Pentanediol - Rodiansono, Rodiansono; Azzahra, Atina Sabila; Mikrianto, Edi; Ridhoni, Arif; Mustari, Ikhsan; Nurfitriani, Anggita; Bodoi, Thea Seventina Desiani; Sanjaya, Rahmat Eko; Suarso, Eka; Ansyah, Pathur Razi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
The selective aqueous phase hydrogenolysis of furfuryl alcohol (FFalc) to 1,5-pentanediol (1,5-PeD) using supported bimetallic ruthenium-tin (Ru-Sn) catalysts on various metal oxide supports (e.g., TiO2, ZnO, ZrO2, Nb2O5, g-Al2O3) and its combination were investigated systematically. The catalysts were prepared via coprecipitation-hydrothermal at 150 oC for 24 h, followed by reduction with H2 at 400 oC for 2 h. Supported Ru-Sn on TiO2(A), g-Al2O3, and ZrO2 catalysts exhibited higher yield of 1,5-PeD (55-69%) than that other catalysts at 180 oC, H2 10-30 bar for 3-5 h. However, those supported catalysts showed poor recyclability after the first reaction run, and therefore further examination on g-Al2O3 supported Ru-Sn was performed. The Ru-Sn catalyst supported on g-Al2O3-metal oxide composites (metal oxides: ZrO2, TiO2(A), TiO2(R), ZnO, Nb2O5, and C) afforded higher FFalc conversion and yield of 1,5-PeD than that of unmodified g-Al2O3 at 180 oC, H2 30 bar for 3 h. Among them, the Ru-Sn/g-Al2O3-TiO2(A) (33%) catalyst could afford the highest yield of 1,5-PeD (80%) at 99% conversion FFalc at 180 oC, H2 10 bar for 5 h. Around 95% of this catalyst can be recycled after the second reaction run and the activity can be restored to initial after reactivation with H2 at 400 oC for 2 h with a 69% yield of 1,5-PeD at 97% FFalc conversion. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).